Technical Standard Based Machine Safety Management System through Component Risk Analysis for Mechanical Hazard Control - Darmawan , Didit; Febriansyah, Putra Angga Dwi; Firmansyah, Rizqi Octavian Nur; Chandra, Risky Febrian; Shaleh, Mohamad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This theoretical study examines the implementation of machine safety management systems based on technical standards through component level risk analysis. Four International Organization for Standardization standards provide the framework: ISO 12100 for risk assessment methodology, ISO 13857 for safety distances, ISO 13849 for control system performance levels, and OSHA 1910.147 for lockout tagout procedures. Component level analysis requires systematic identification of every moving part, estimation of injury severity, exposure frequency, and hazard avoidance probability. This analysis determines whether fixed guards, interlocked guards, or presence sensing devices are appropriate. Verification and validation procedures are mandatory to confirm that installed safeguards meet specification requirements. Documentation serves as legal evidence of due diligence. Legacy machinery demands alternative approaches due to missing technical documentation. Small enterprises may adopt phased implementation prioritizing high risk machinery. Cross functional collaboration between engineering, safety departments, and worker representatives determines implementation success. Machinery safety audits require personnel with mechanical engineering backgrounds certified in functional safety.